Open-Switch Fault Diagnosis and Tolerant Control Methods for a Vienna Rectifier Using Bi-Directional Switches - Lee, June Seok; Lee, Kyo Beum (2018 IEEE Energy Conversion Congress and Exposition, ECCE 2018, 2018)
This paper proposes open-switch fault diagnosis and tolerant control methods for a Vienna rectifier using bidirectional switches. The proposed diagnosis method detects the open-switch fault by using only the input currents without the additional devices. In addition, a position of the open-switch fault detected by the proposed diagnosis method is used to apply the proposed tolerant control. The proposed tolerant control is implemented by modifying the reference voltages of the Vienna rectifier. The proposed tolerant control can mitigate the ripple component in the dc-link voltage and improve the performance in terms of the current total harmonic distortion compared to when any tolerant control is not applied. The effectiveness and performance of the proposed diagnosis and tolerant control methods are verified by simulation.
Keywords: Bidirectional switch; DC-link voltages; Diagnosis methods; Open switch fault diagnosis; Reference voltages; Switch faults; Total harmonic distortion (THD); Vienna rectifiers; Fault Diagnosis; Open-switch fault; Tolerant control; Vienna rectifier